Hydrolytically Degradable Thiol–ene Hydrogels for Protein Release. Issue 1 (23rd August 2013) - Rehmann, Matthew S.; Garibian, Andrew C.; Kloxin, April M.; Bowman, Christopher N.; Horkay, Ferenc
Summary A new degradable PEG‐diester‐dinorbornene/PEG‐triester‐trithiol hydrogel was evaluated for protein release. The hydrogel polymerized rapidly with seconds of UV irradiation and subsequently hydrolytically degraded in aqueous buffer over the course of approximately 3 weeks. Further, the hydrogel enabled the encapsulation and release of a model protein, bovine serum albumin (BSA), over 7 days with ∼ 90% released at 48 h. This study serves as a proof‐of‐concept for the creation of hydrolytically degradable, PEG‐ester‐thiol‐based hydrogels by a photoinitiated step growth mechanism for protein release. With this approach, degradation and release rates could be tuned by varying the monomer molecular weight and functionality in future studies.